Consumption and life satisfaction at different levels of economic development - DUMLUDAĞ, DEVRİM (Springer Verlag, 2015)
The present paper proposes to examine the impact of varying consumption categories on life satisfaction at different levels of development by focusing on transition countries and developed European countries. This is done by looking at the Life in Transition Surveys (I and II) that include reported life satisfaction, as well as control variables such as gender, household size, marital status, age, and education (EBRD, http://www.ebrd.com/pages/research/publications/special/lifeintransition.shtml2007; http://www.ebrd.com/pages/research/publications/special/transitionII.shtml2011). The study includes several categories such as expenditures on food, education, and durables. The paper also examines the impact of the reduction in several consumption items on life satisfaction after the 2008 crisis. The econometric results reveal that not all consumption items are statistically significant as determinants of life satisfaction. At different levels of development, the relationship between life satisfaction and consumption differs and some consumption categories have a negative impact on life satisfaction. Finally, the reduction in the level of consumption due to economic crises has a negative impact on life satisfaction. © 2015, Springer-Verlag Berlin Heidelberg.
Keywords: Consumption; Developed countries; Life satisfaction; Transition countries